2022
DOI: 10.1088/1748-0221/17/07/c07005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of an X-ray photon counting detector

Abstract: This paper presents the experimental test results of the X-ray photon counting detectors based on our pixel readout ASIC. The chip integrates a 64 × 128 array of pixels in the size of 150 µm × 150 µm and each pixel consists of four 12-bit energy windows. Two types of CdTe detectors have been bump bonded to the ASICs and have been tested. The electronic characteristics of the readout chip were evaluated first by injecting charge through the calibration capacitors. The non-uniformity of the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Lixiang and his team members [12] suggested that CVS during the SARS-CoV-2 Outbreak in University Students: A Comparison between Online Courses and Classroom Lectures. The main aim of the paper is to compare the wide spread of CVS among students taking online classes and Chinese students going to school after lockdown relaxation.…”
Section: Literature Surveymentioning
confidence: 99%
“…Lixiang and his team members [12] suggested that CVS during the SARS-CoV-2 Outbreak in University Students: A Comparison between Online Courses and Classroom Lectures. The main aim of the paper is to compare the wide spread of CVS among students taking online classes and Chinese students going to school after lockdown relaxation.…”
Section: Literature Surveymentioning
confidence: 99%
“…It is possible to have greater precision. Kumar [12] adopted methodology used in this model is GPS location. Students' whereabouts are determined using GPS on their phones.…”
Section: Literature Surveymentioning
confidence: 99%